2014
DOI: 10.4149/bll_2014_146
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of preemptive analgesic effects of curcumin and diclofenac

Abstract: Abstract:Objective: Preemptive analgesia is an antinociceptive treatment that prevents central sensitization. Antinociceptive effects of diclofenac are well-known. The aim of this study was to investigate preemptive analgesic effects of curcumin and diclofenac, before acute and infl ammatory induced pain in rat model. Material and methods: Fourty eight old female (n = 6 in each group) Wistar Albino rats were included in the study. Paw movements in response to paw fl inching in response to formalin injection or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Nurullahoglu et al [ 176 ] suggested the preemptive analgesic effects of curcumin on acute thermal and inflammation-induced pain in female Wistar Albino rats. Furthermore, the study compared the preemptive effects of curcumin with intraperitoneal administration of diclofenac (10 mg/kg), a non-steroidal anti-inflammatory drug [ 180 ].…”
Section: Curcumin and Postoperative Pain And Preemptive Analgesia—preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurullahoglu et al [ 176 ] suggested the preemptive analgesic effects of curcumin on acute thermal and inflammation-induced pain in female Wistar Albino rats. Furthermore, the study compared the preemptive effects of curcumin with intraperitoneal administration of diclofenac (10 mg/kg), a non-steroidal anti-inflammatory drug [ 180 ].…”
Section: Curcumin and Postoperative Pain And Preemptive Analgesia—preclinical Studiesmentioning
confidence: 99%
“…Diclofenac exerts controversial preemptive effects, with some studies, showing no differences in the effects in between pre- and postoperative diclofenac-treated patients undergoing laparoscopic tubal ligation [ 177 ], while other studies reported that preoperative administration of diclofenac along with ketorolac and piroxicam reduced postoperative pain in patients undergoing laparoscopy [ 181 , 182 ]. Based on Nurullahoglu et al’s [ 176 ] study, both curcumin and diclofenac exerted preemptive analgesic effects. Bulboacs et al [ 175 ] demonstrated the preemptive effects of curcumin in a rodent migraine model.…”
Section: Curcumin and Postoperative Pain And Preemptive Analgesia—preclinical Studiesmentioning
confidence: 99%
“…Such findings suggest that the GABA and opioid receptor systems may be [5,6,24]. In addition, oral curcumin reduced the formalin-induced flinching response, thermal hyperalgesia and neuropathic pain [25][26][27]. Intravenous curcumin attenuated visceral nociception [28].…”
Section: Discussionmentioning
confidence: 98%
“…In an experimental study performed by Nurullahoglu et al [ 46 ], curcumin suspension in a dose of 400 mg/kg b.w. prepared in 5% ethanol solution, proved more potent than diclofenac alone in the early phase of pain on formalin test.…”
Section: Discussionmentioning
confidence: 99%